THE EFFECTS OF SUPERVISOR SUPPORT ON PRESENTEEISM AMONG GOVERNMENT EMPLOYEES IN PUTRAJAYA - Mastura Mohamad; Sharifah Norhuda Syed Wahid; Hazlin Hasan (International Journal of Accounting, Finance and Business, 2022)
The purpose of this study was to investigate the effects of supervisor support onpresenteeism among the government employees as previous research has shown mixed findingson the notion that supervisor support is crucial in motivating and inspiring employees.Meanwhile, presenteeism has become a worldwide phenomenon and linked to the loss ofproductivity among employees more so than absenteeism, thus the need for the investigation.The regression analysis approach using IBM-SPSS AMOS 24 software was used to determinethe effects of supervisor support on presenteeism of government employees. 108 respondentswere selected using stratified sampling technique answered a set of questionnaires. The studyfound positive significant effect of supervisor support on presenteeism (β ̂ = 0.45, p = < 0.001)whereby presenteeism of employees has been expected to increase when supervisor’s supportwas increased. The study concluded that the role of employer in an organization is verysignificant, thus, a better understanding on supervisor support would assist the organization intackling issues that contribute further to presenteeism. By understanding these coremanagement issues, the organization is expected to provide efficient service to the public, henceimproved productivity of the public sector.